1985
DOI: 10.1002/jsfa.2740360604
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gamma radiation on ochratoxin production by the fungus Aspergillus ochraceus

Abstract: Mycelial discs of the fungus Aspergillus ochraceus NRRL 3174 were exposed to gamma irradiation and then incubated on synthetic medium (SM). Growth rate, mycelial dry weight and ochratoxin production were measured. A delay in mycelial growth of 24 and 48h over the control occurred following irradiation of mycelial discs with 150 and 200 krad, respectively. No growth occurred from discs exposed to 300 krad. An increase in ochratoxin production occurred on the SM from cultures developing from discs of mycelium wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 12 publications
0
17
0
2
Order By: Relevance
“…The effect of radiation on mycotoxin production was studied mainly concerning aflatoxin [3] and ochratoxin [32]. Aziz [4] revealed that UV-radiation induced synthesis of mycotoxins (aflatoxins and ochratoxin A) by nonNational Center for Radiation Research and Technology, Food Microbiology Department, P.O.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of radiation on mycotoxin production was studied mainly concerning aflatoxin [3] and ochratoxin [32]. Aziz [4] revealed that UV-radiation induced synthesis of mycotoxins (aflatoxins and ochratoxin A) by nonNational Center for Radiation Research and Technology, Food Microbiology Department, P.O.…”
Section: Introductionmentioning
confidence: 99%
“…From this study, it is clear that all metabolities of nontoxigenic fungal strains A. flavus EP-63, A. niger EN-200 and A. ochraceus P-157 which were able to synthesize mycotoxins under the influence of UV radiation decreased greatly the percentage of plant seed germination (5-16%) as compared to control (83-98%). Most of the work dealing with the effect of radiation on fungi has been focused on asexual spores [4,7,18,19,24]. This can be attributed mainly to the importance of the spore as infesting propagules and their common structure as single cell with one nucleus.…”
Section: Effect Of Uv Radiation On Mycotoxin Biosynthesis By Nonmycotmentioning
confidence: 99%
“…This can be attributed mainly to the importance of the spore as infesting propagules and their common structure as single cell with one nucleus. Several studies [7,11,19] revealed that higher concentrations of aflatoxins were produced by strains of A. flavus and A. parasiticus and ochratoxin A by A. ochraceus in irradiated foods than in unirradiated controls. The role of radiation, especially UV in the mutation of fungal spores is nowadays an interesting research point.…”
Section: Effect Of Uv Radiation On Mycotoxin Biosynthesis By Nonmycotmentioning
confidence: 99%
See 1 more Smart Citation
“…There are number of conflicting reports which suggest that the production of mycotoxins is either increased [28,34], decreased [35,36,38] or unaffected [27] after irradiation of grains or spores under various laboratory conditions. The present study was designed to evaluate the relationships between the addition of iron, copper or zinc to crushed corn and the growth rate and aflatoxin B 1 production by Aspergillus flavus after different storage periods.…”
Section: Introductionmentioning
confidence: 99%